2019
DOI: 10.1021/acsphotonics.9b00519
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Measurement in Plasmonic Nanoapertures Used for Optical Trapping

Abstract: Plasmonic nanoapertures generate strong field gradients enabling efficient optical trapping of nanoobjects. However, because the infrared laser used for trapping is also partly absorbed into the metal leading to Joule heating, plasmonic nano-optical tweezers face the issue of local temperature increase.Here, we develop three independent methods based on molecular fluorescence to quantify the temperature increase induced by a 1064 nm trapping beam focused on single and double nanoholes milled in gold films. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 68 publications
5
91
0
Order By: Relevance
“…Xu et al predicted a maximum temperature increase of 6°C for double nanoaperture at an incident laser intensity of 6.67 mW/μm 2 [65]. More recently, Jiang et al combined fluorescence spectroscopy with OT in order to locally measure the temperature of single and double nanoapertures [66]. The authors showed that the temperature can increase by around 10°C at 2 mW/μm 2 incident laser intensity for a double nanoaperture and 20°C under 5 mW/μm 2 illumination for a single nanoaperture [66].…”
Section: Advantages and Disadvantages Of Potmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al predicted a maximum temperature increase of 6°C for double nanoaperture at an incident laser intensity of 6.67 mW/μm 2 [65]. More recently, Jiang et al combined fluorescence spectroscopy with OT in order to locally measure the temperature of single and double nanoapertures [66]. The authors showed that the temperature can increase by around 10°C at 2 mW/μm 2 incident laser intensity for a double nanoaperture and 20°C under 5 mW/μm 2 illumination for a single nanoaperture [66].…”
Section: Advantages and Disadvantages Of Potmentioning
confidence: 99%
“…More recently, Jiang et al combined fluorescence spectroscopy with OT in order to locally measure the temperature of single and double nanoapertures [66]. The authors showed that the temperature can increase by around 10°C at 2 mW/μm 2 incident laser intensity for a double nanoaperture and 20°C under 5 mW/μm 2 illumination for a single nanoaperture [66]. Notably, the majority of POT experiments are performed using a base wafer material of either fused silica or silicon.…”
Section: Advantages and Disadvantages Of Potmentioning
confidence: 99%
“…However, in some cases where manipulation of temperature-sensitive bioparticles is needed, nano-aperture based POTs, which enable stable trapping with low incident intensity are introduced, 16,18,19,[23][24][25] thereby minimizing phototoxicity. 25 By arraying nano-aperture units 16,22,26,27 in metallic substrates, many trapping sites can be activated at the same time, permitting simultaneous analysis of several particles locally trapped in well-defined positions of the plasmonic nanostructure and pro-viding an alternative method of particle crystallization. Therefore, selectivity of biomolecule trapping in a heterogeneous environment could have a significant impact on defining structural information during transition paths, 28 leading among other things, to more precise drug design.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] Since their inception in 2002, ZMWs have been widely used for a large range of biophysical and biochemical applications, including DNA sequencing, [17][18][19] enzymatic reaction monitoring, [20][21][22] proteinprotein interaction, [23][24][25][26][27] nanopore sensing, [28][29][30][31][32] Förster resonance energy transfer, [33][34][35] biomembrane investigations, [36][37][38][39][40] and nano-optical trapping. [41][42][43][44] However, all these applications require a proper surface passivation and/or functionalization of the ZMW in order to avoid the unwanted adsorption of the fluorescent molecules onto the ZMW surface that would impede the experiments. While extensive literature exists for passivating glass surfaces for single molecule fluorescence microscopy, [45][46][47][48][49][50][51]…”
mentioning
confidence: 99%